Testing the Causal Relationship between Economic Diversification and Exchange Rate in Algeria during the Period: 2000-2021Using the Methodology of Toda &Yamamoto - mekahlia, raid; cherayett, kamel; benlahbib, Taha (Journal of Research in Finance and Accounting, 2023)
This study aims to identify trends of the causal relationship between economic diversification and real effective exchange rate in Algeria during the period 2000 and 2021. For this purpose, Toda and Yamamoto (1995) Methodology is used to test causality in the long run, which is based on estimating Augmented Vector autoregression model. The study concluded that there is a unidirectional causal relationship going from economic diversification towards real effective exchange rate in the long-run which means that the diversification of the economic activity in Algeria is contributing in enhancing the value of exchange rate Dinars in front of other foreign currencies. The study also stressed the need to benefit from the international experiments in the field of economic diversification for the sake of strengthen the economic activity.